2005
DOI: 10.1124/mol.104.008953
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hydroxylamine on KATPChannels in Vascular Smooth Muscle and Underlying Mechanisms

Abstract: Hydroxylamine (HA) is a putative intermediate in the conversion of L-arginine to nitric oxide (NO). HA was reported to cause the relaxation of precontracted aorta strips; however, the ionic mechanisms of HA-induced vasorelaxation were not yet known. In the present study, the whole-cell patch-clamp technique was used to examine the effects of HA on ATP-sensitive K ϩ (K ATP ) currents and membrane potentials in vascular smooth muscle cells from rat mesenteric arteries and underlying mechanisms. It was found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Hcy at a concentration range of 1, 100, and 300 lM did not alter the amplitude of outward K + currents (n = 5-8 for each concentration, Fig. Another way to increase the concentration of superoxide radicals is to add a free radical generation system-a mixture of hypoxanthine (HX, 100 lM) and xanthine oxidase (XO, 0.01 UÁmL À1 ) [24]. In porcine coronary artery smooth muscle cells it was reported that Hcy was effective only in the presence of NADH in the pipette a substrate of NADH-oxidases, generating superoxide anions [11].…”
Section: Resultsmentioning
confidence: 99%
“…Hcy at a concentration range of 1, 100, and 300 lM did not alter the amplitude of outward K + currents (n = 5-8 for each concentration, Fig. Another way to increase the concentration of superoxide radicals is to add a free radical generation system-a mixture of hypoxanthine (HX, 100 lM) and xanthine oxidase (XO, 0.01 UÁmL À1 ) [24]. In porcine coronary artery smooth muscle cells it was reported that Hcy was effective only in the presence of NADH in the pipette a substrate of NADH-oxidases, generating superoxide anions [11].…”
Section: Resultsmentioning
confidence: 99%
“…H 2 S is a vasorelaxant factor that acts through K ATP channels causing smooth muscle relaxation 1,41 and playing a role in uterine contractility. 27 Recent placental studies provided contradictory findings probably because of the small sample size of these studies.…”
Section: Discussionmentioning
confidence: 99%
“…In some animals, such as the mouse, K ATP channels are not involved at all in the response. H 2 S may also signal via other pathways, such as activation of adenylate cyclase, which, in turn, inhibits superoxide formation, NADPH oxidase, and Rac 1 activity (112); it may produce intracellular acidosis and alter intracellular redox status, stimulate an anion exchanger (97), or operate through Ca 2ϩ -dependent K ϩ (K Ca ) channels (77,161,206). Relaxation of rat aorta by exogenous H 2 S does not depend on vascular prostaglandin synthesis, PKC, or cAMP, nor does it involve superoxide or H 2 O 2 production (77,78,204).…”
Section: H 2 S Biologymentioning
confidence: 99%